2009
DOI: 10.1128/iai.00280-09
|View full text |Cite
|
Sign up to set email alerts
|

The Posttranslocation Chaperone PrsA2 Contributes to Multiple Facets ofListeria monocytogenesPathogenesis

Abstract: Listeria monocytogenes is an intracellular bacterial pathogen whose virulence depends on the regulated expression of numerous secreted bacterial factors. As for other gram-positive bacteria, many proteins secreted by L. monocytogenes are translocated across the bacterial membrane in an unfolded state to the compartment existing between the membrane and the cell wall. This compartment presents a challenging environment for protein folding due to its high density of negative charge, high concentrations of cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
173
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(175 citation statements)
references
References 84 publications
2
173
0
Order By: Relevance
“…Previous studies have demonstrated that Nuc requires PPIase activity for optimal protein folding (3,4). Based on this observation and the fact that PPIase-mediated folding is required for subsequent activity of secreted virulence factors in a number of bacterial pathogens (8)(9)(10)(11)(27)(28)(29)(30), we hypothesized that a staphylococcal PPIase may be required for the activity of Nuc. To begin to investigate this, we examined the genome of the community-associated methicillin-resistant S. aureus (MRSA) isolate USA300 for genes that encode PPIase enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that Nuc requires PPIase activity for optimal protein folding (3,4). Based on this observation and the fact that PPIase-mediated folding is required for subsequent activity of secreted virulence factors in a number of bacterial pathogens (8)(9)(10)(11)(27)(28)(29)(30), we hypothesized that a staphylococcal PPIase may be required for the activity of Nuc. To begin to investigate this, we examined the genome of the community-associated methicillin-resistant S. aureus (MRSA) isolate USA300 for genes that encode PPIase enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought to assist in the refolding of proteins as they are exported from the bacterial cell. PrsA has been well studied in two bacterial pathogens, Listeria monocytogenes and Streptococcus pyogenes, where alteration of prsA levels (either increased or decreased) leads to defects in protein secretion and/or virulence of the organism (7)(8)(9)(10). The cyclophilins are by far the least-studied and least well understood group of PPIases in bacteria.…”
mentioning
confidence: 99%
“…PrsA2 was shown to be important for L. monocytogenes pathogenesis by stimulating the activity and assuring the stability of LLO and PC-PLC. 139 Absence of PrsA2 induces significant virulence attenuation in the mouse model and deficient bacterial cell-to-cell spread in host cell lines. PrsA2 is thus required for the stabilization and optimal activity of L. monocytogenes-secreted factors involved in vacuole escape.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…As chaperones and foldases PPIases are involved in diverse protein-protein interactions that are short lived, difficult to entangle, and pleiotropic in their biological impact on bacterial physiology. Hence, it is not surprising that PPIases also very often correlate with virulence in pathogenic bacteria (Alonzo et al, 2009;Behrens-Kneip, 2010;Moro et al, 1995;Obi et al, 2011). This has become even more evident since the identification of macrophage infectivity potentiator (Mip) of Legionella pneumophila, as the first virulence-associated PPIase, and has opened the way to the analysis of bacterial FKBPs under the aspect infections with implications in alternative drug design strategies Fischer et al, 1992Fischer et al, , Ünal et al, 2011Ünal and Steinert, 2014).…”
Section: Introductionmentioning
confidence: 99%